Experimental Investigation and NSGA-III Multi-Criteria Optimization of 60CrMoV18-5 Cold-Work Tool Steel Machinability Under Dry CNC Hard Turning Conditions - Nikolaos A. Fountas; Ioannis G. Papantoniou; Dimitrios E. Manolakos; Nikolaos M. Vaxevanidis (Machines)
This work concerns an experimental investigation dealing with the machinability of 60CrMoV18-5 cold-work tool steel under dry CNC hard turning conditions using a CBN cutting insert. A response surface experiment based on the central composite design was set to conduct dry CNC hard-turning experiments with three different levels for cutting conditions, cutting speed Vc (m/min), feed rate f (mm/rev), and depth of cut α (mm) while selecting main cutting force and surface roughness Ra as the two machinability responses. The results were analyzed by applying analysis of variance (ANOVA). The effect of cutting conditions on main cutting force and surface roughness was studied through contour plots. Full quadratic regression models were generated to model the relationships between inputs and outputs. Finally, the NSGA-III algorithm was applied to simultaneously optimize the selected machinability parameters by providing beneficial values for determining cutting conditions. The results have shown that surface roughness is mainly affected by feed rate and cutting speed, whereas main cutting force is affected by depth of cut and feed rate.